2017
DOI: 10.1002/hbm.23512
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal investigation of triple network connectivity in patients with 22q11DS and association with executive functions

Abstract: Large-scale brain networks play a prominent role in cognitive abilities and their activity is impaired in psychiatric disorders, such as schizophrenia. Patients with 22q11.2 deletion syndrome (22q11DS) are at high risk of developing schizophrenia and present similar cognitive impairments, including executive functions deficits. Thus, 22q11DS represents a model for the study of neural biomarkers associated with schizophrenia. In this study, we investigated structural and functional connectivity within and betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 84 publications
2
12
1
Order By: Relevance
“…In individuals with 22q11DS, the DMN has been associated with prodromal symptoms [ 21 ], sustained attention [ 21 ] and reciprocal social behaviors [ 23 ]. It is not clear why we observed increased functional connectivity between these DMN regions, while several other studies [ 23 26 ] of 22q11DS have observed decreased functional connectivity between these regions. This may be attributable, in part, to our implementation of measurements within each subject’s native brain space.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…In individuals with 22q11DS, the DMN has been associated with prodromal symptoms [ 21 ], sustained attention [ 21 ] and reciprocal social behaviors [ 23 ]. It is not clear why we observed increased functional connectivity between these DMN regions, while several other studies [ 23 26 ] of 22q11DS have observed decreased functional connectivity between these regions. This may be attributable, in part, to our implementation of measurements within each subject’s native brain space.…”
Section: Discussioncontrasting
confidence: 89%
“…Results of these studies indicate anomalous connectivity in frontal lobe connections [ 20 ] and parieto–occipital connections [ 20 22 ]. Decreases in functional connectivity have also been observed, in partially overlapping samples, in the default mode [ 23 26 ], salience [ 24 ] and frontal–parietal networks [ 22 , 24 ]. In a modularity analysis of overall functional network organization, Scariati and colleagues [ 27 ] observed increased modular segregation across superior parietal, frontal and inferior temporal lobes in individuals with 22q11DS.…”
Section: Introductionmentioning
confidence: 99%
“…Dysconnectivity of thalamic-hippocampal circuitry 13 has been reported in 22q11.2 deletion carriers, with prominent under-connectivity of the default mode network (DMN), which was predictive of prodromal psychotic symptomatology 14,15 . Impaired connectivity of long-range connections within the DMN has also been reported by other studies 16 . A single 16p11.2 study has showed a decrease in connectivity of fronto-temporal and -parietal connections in deletion carriers 17 .…”
Section: Introductionsupporting
confidence: 81%
“…Dysconnectivity of thalamic-hippocampal circuitry 17 has been reported in 22q11.2 deletion carriers, with prominent under-connectivity of the default mode network (DMN), which was predictive of prodromal psychotic symptomatology 18,19 . Impaired connectivity of long-range connections within the DMN has also been reported by other studies 20 . A single 16p11.2 study has shown a decrease in connectivity of frontotemporal and -parietal connections in deletion carriers 21 .…”
supporting
confidence: 81%